European economic and social constitutionalism after the Treaty of Lisbon / edited by Dagmar Schiek, Ulrike Liebert and Hildegard Schneider. - Schiek, Dagmar; Liebert, Ulrike; Schneider, Hildegard (Cambridge University Press, 2011)
European studies frequently regard the economic and social dimensions of EU integration as diametrically opposed, maintaining that this state of affairs is beyond change. This edited collection challenges this perceived wisdom, focusing on the post-Lisbon constitutional landscape. Taking the multi-layered polity that is Europe today as its central organising theme, it examines how the social and the economic might be reconciled under the Union's different forms of governance. The collection has a clear structure, opening with a theoretical appraisal of its theme, before considering three specific policy fields: migration policy and civic integration, company law and corporate social responsibility and the role of third sector providers in public healthcare. It concludes with three case studies in these fields, illustrating how the argument can be practically applied. Insightful and topical, with a unique interdisciplinary perspective, this is an important contribution to European Union law after the Lisbon Treaty.